On ‘People and the Human Condition’: Tom Stannage and Labour History - Oliver, Bobbie (University of Western Australia, 2015)
Reading Tom Stannage's The People of Perth for the first time in 1987, I was particularly moved by two stories. One was of William Holmes, a stonemason employed on the Mill Street Jetty, whose conditions of employment were changed by his boss after he was contracted and involved working waist-deep in water. When Holmes became seriously ill and was unable to perform his duties, his employer took him to court and forced him to return to work. The other story was of Catherine Kelly, an Irish immigrant girl, who bore her illegitimate baby in a backyard cesspit where it drowned. Though she was charged with the murder of her infant, Kelly was found not guilty and set free - although 'free' was hardly a term that could be applied to the life of a servant in Swan River Colony.